Phage display: Binding confirmation - Kristie Nybo (BioTechniques, 2010)
This month's question from the Molecular Biology Forums (online at molecularbiology.forums.biotechniques.com) comes from the “Protein Methods” section. Entries have been edited for concision and clarity. Mentions of specific products and manufacturers have been retained from the original posts, but do not represent endorsements by, or the opinions of, BioTechniques.